Efeitos do estresse pré-natal sobre a função pulmonar e parâmetros inflamatórios em camundongos expostos a um modelo de asma - Vargas, Mauro Henrique Moraes (2015)
Introduction: Adversities faced during the prenatal period can be related to the onset of diseases in adulthood. However, little is known about its effects on the respiratory system. Aims: To assess the effects of restraint prenatal stress, in two different moments of pregnancy, on pulmonary function and inflammatory profile in male and female mice exposed to a ovalbumin (OVA) induced asthma model. Methods: Male and female BALB/c mice were divided into 3 groups: control (CON), prenatal stress from the second week of pregnancy (PNS1) and prenatal stress on the last week of pregnancy (PNS2). Pups were weighted on 3 different moments (days 1, 10 and 21). As adults, the fear/anxiety behavior was evaluated in the open field (between days 50° and 54°). The ovalbumin-induced asthma model was performed at day 56, followed by the analysis of lung function (airway resistance, tissue damping and elastance), collection of bronchoalveolar lavage fluid, total and differential cell count and inflammatory cytokines evaluation. The left lung was removed and processed for histological analysis. Results: There was a significant decrease (p<0.05) in the number of entries and time spent in the central quadrant only in PNS1 group compared to controls. Females (PNS1) also presented an improvement in the lung function, measured as airway resistance, tissue damping and pulmonary elastance (p<0.05). When female differential cell count was analyzed, PNS1 group showed a significant increase in the percentage of neutrophils (p<0.01), lymphocytes (p<0.05) and a significant decrease of eosinophils (p<0.05) when compared to the control group. There was also a decrease in the BAL inflammatory cytokines, including a significant reduction in IL-5 and IL-13 in males of PNS1 (p<0.001 and p<0.01) and PNS2 (p<0.01 and p<0.01) when compared to controls. In females, a significant reduction in the secretion of IL-4, IL-5 and IL-13 in both PNS1 (p<0.05, p<0.001 and p<0.01) and PNS2 (p<0.01, p<0.001 and p<0.05) were demonstrated. Conclusion: The results of this study indicate that prenatal stress, from the second week of pregnancy (PNS1), reduces the impact of asthma development in adult female mice, showing an improved pulmonary function and a lower allergic inflammatory response in the lungs.